The effect of clays on the mechanical properties of dynamically revulcanized blends composed of ground tire rubber/high-density polyethylene (2024)
This study examines the impact of adding Cloisite 20A and Halloysite clay on the mechanical properties of dynamically revulcanized blends composed of high-density polyethylene (HDPE) and ground tire rubber (GTR), which have been previously devulcanized via microwaves. Blends were prepared, containing different concentrations of the phases. Halloysite clay seems to have acted as a compatibilizer agent between the phases of the blends, whereas Cloisite 20A clay seems to have acted as a reinforcement in the revulcanized blends. However, slight deviations were noticed in the variations in the phases’ concentrations. This study explored the possibility of utilizing end-of-life tires in polymeric blends.